Surgical Outcomes of Cystectomy Using Oxidized Regenerated Cellulose With and Without Drainage in Endometrioma Treatment - Setiawan, Marcel Ezra; Emeraldi, Malvin; Asadi, Agus Surur; Putera, Aditya Rangga; Puspitasari, Rany Ayu; Marwali, Muhammad Luky Satria Syahbana (Indonesian Journal of Obstetrics and Gynecology, 2025)
Objective: Our study aims to compare cystectomy and drainage using oxidized regenerated cellulose (ORC) in reducing endometrioma recurrence after surgery. Methods: A retrospective cohort study included patients with endometrioma who undergo laparoscopic surgical management (cystectomy and drainage) with ORC from June 2020 – January 2023. All patients were followed up a year for recurrence rate. Recurrence was assessed based on symptoms and ultrasound criteria. All data were analyzed using SPSS version 26.0. Results: Twenty-five patients were included in the cystectomy group and twenty-seven patients were included in the drainage group. The recurrence rate was higher in patients who underwent drainage (29.6%, n = 8) than in patients who underwent cystectomy (20%, n = 5). The researchers found the result was not significant (p > 0.05) in the recurrence rate between the two groups. Conclusion: In this study, the use of oxidized regenerated cellulose showed no difference in recurrence rates in cystectomy with ORC and drainage with orc. Keywords: endometrioma, cystectomy, drainage, oxidized regenerated cellulose